ACCOUNTING IMPLICATIONS OF THE BUSINESS CYCLE. - Eppston, Harold A. (The Accounting Review, 1941)
Accounting principles and practices, being pragmatic in origin and conditioned by reality, resist codification into hard and fast rules. Yet like all parts of culture these principles and practices manifest the social lag and do not quite keep up with all the rapid changes that occur in the economic scene. Impatient critics sometimes wish to scrap more of these principles and practices than is required for necessary adaptation. They forget that much in the current scene was developed from the past, that the past is always with everyone and that many of established practices have the same cogency today as yesteryear. Business expansion in the form of new capital equipment mainly takes place during an upswing. It augments and accelerates the upswing and perhaps helps create it. The expansion may occur for any number of reasons, technological, psychological, political, economic or for random causes. When management builds a plant anticipating a certain series of schedules of production, the value of that plant is measured by what it costs.